Effect of repeated preheating on monomer elution from a bulk-fill composite resin - Samet Atasoy; Serdar Akarsu (Tabriz University of Medical Sciences, 2023)
Background. Due to incomplete polymerization of composite resin restorations, residual monomers adversely affect their mechanical properties and biocompatibility. Preheating of composite resins is advised to increase the degree of conversion and reduce monomer elution. This study aimed to analyze the effect of preheating and repeated preheating on the amount of monomer released from a bulk-fill composite resin. Methods. Forty samples were prepared using Filtek One Bulk Fill Restorative composite resin. Samples in one group were fabricated at room temperature, whereas the composite resins in the other groups were cured after 1, 10, or 20 repeated preheating cycles (55 °C), 10 in each group. Eluted urethane dimethacrylate (UDMA) and bisphenol-A-glycidylmethacrylate (BisGMA) monomers were measured with high-performance liquid chromatography (HPLC) 24 hours and 30 days after immersion. The data were evaluated using one-way ANOVA and post hoc Tukey tests. Paired-sample t tests were used to test the differences between time intervals. Results. At both time intervals, the greatest amounts of released BisGMA, UDMA, and total monomers were obtained from the control group, whereas 10 preheating cycles resulted in the least monomer elution. The decrease in monomer elution was not statistically significant after 10 preheating cycles compared with that after one preheating cycle (P>0.05). The group with 20 preheating cycles showed a greater amount of monomer elution compared to that with 1 and 10 cycles, which was statistically significant (P < 0.05). The amount of released monomers on day 30 was significantly higher than on day 1 (P<0.01). Conclusion. Preheating of the bulk-fill composite resin was shown to be effective in reducing monomer elution. However, monomer elution was adversely affected after repeated preheating cycles of 20.